PEMBANGUNAN KEARSIPAN DALAM KERANGKA OTONOMI DAERAH DI INDONESIA: Array - Khoerun Nisa Fadillah (Jurnal Kearsipan, 2010)
This research aims to find answers of two fundamental questions, namely, how is the archival development policy performed by the Indonesian government during the regional autonomy era and how can it be developed to support the implementation of regional autonomy in Indonesia. This is a descriptive qualitative research. Data collection used was literature, observations, and documentation techniques. The technique of data analysis used was inductive analysis techniques. The results showed several important conclusions, namely: 1) The archival development policy which has been applied by the Indonesiangovernment in the era of regional autonomy are: a) transfer of archival issues to local governments as their obligatory functions, b) arrangement of archival institutions as a the most likely consequence of the above mentioned policy, c) strategy of archival development which is focused on the roles of local governments; 2) The government has to cope with several obstacles and challenges in carrying out archival development, such as: a) some regencies/cities do not have any archival institutions as mandated by The Government Regulation Number 41 of 2007 concerning Local Apparatus Organization, b) there isn’t anyimplementing regulations governing the establishment of archival institutions, c) there isn’t any guideline for minimum service standards of archival services, d) there isn’t any optimal guidances, supervisions, consultations, and implementation of archival system in the central and local government, e) regulations that anticipate the demands of good governance and implementation of regional autonomy is inadequate; 3) the archival development models carried out to support the implementation of regional autonomy in Indonesia are, a) having minimum archival service standard as a measuring rod of archival performance at localgovernments, b) setting local governments as the main actors of development, c) taking a finicky priority in designing archival development strategies and locus priority in establishing the pattern of institutional relationship in order that archival development can be run effectively and efficiently.